Analisis Peran Penyuluh Dalam Meningkatkan Partisipasi Masyarakat Terhadap Program Keluarga Berencana Di Kota Palembang - Marina Marina; Eni Murdiati; Hartik Utami Fitri (Journal of Innovative and Creativity, 2025)
This study aims to analyze the role of family planning (KB) counselors in increasing community participation in the family planning program in Palembang City. The family planning program is one of the government's efforts to control population growth and improve family welfare. The success of this program depends heavily on active community participation and the effectiveness of outreach programs conducted by field officers. The research method used was a qualitative method with a descriptive approach. Data were obtained through in-depth interviews, observations, and documentation from family planning counselors and the program's target community. The results indicate that family planning counselors play a strategic role in providing information, building awareness, and motivating community participation in the family planning program. However, various obstacles remain, such as a lack of resources, varying levels of community education, and cultural challenges that impact the effectiveness of outreach programs. Therefore, more innovative and adaptive outreach strategies are needed to increase community participation comprehensively.